Effect of femtosecond laser-assisted steepest-meridian clear corneal incisions on preexisting corneal regular astigmatism at the time of cataract surgery - Chen, Wei (Int J Ophthalmol, 2020)
AIM: To investigate the clinical efficacy and safety of femtosecond laser-assisted steepest-meridian clear corneal incisions for correcting preexisting corneal astigmatism performed at the time of cataract surgery. METHODS: This prospective case series study comprised consecutive age-related cataract patients with corneal regular astigmatism (range: +0.75 to +2.50 D) who had femtosecond laser-assisted steepest-meridian clear corneal incisions (single or paired). Corneal astigmatism was performed with the Pentacam preoperatively and 3mo postoperatively. Total corneal astigmatism and steepest-meridian measured in the 3-mm central zone were used to guide the location, size and number of clear corneal incision. The vector analysis of astigmatic change was performed using the Alpins method. RESULTS: Totally 138 eyes of 138 patients were included. The mean preoperative corneal astigmatism was 1.31±0.41 D, and was significantly reduced to 0.69±0.34 D (equivalent to difference vector) after surgery (P<0.01). The surgically-induced astigmatism was 1.02±0.54 D. The correction index (ratio of target induced astigmatism and surgically-induced astigmatism: 0.72±0.36) as well as the magnitude of error (difference between surgically-induced astigmatism and target induced astigmatism: -0.29±0.51) represented a slight under correction. For angle of error, the arithmetic mean was 1.11±13.70, indicating no significant systematic alignment errors. CONCLUSION: Femtosecond-assisted steepest-meridian clear corneal incision is a fast, customizable, adjustable, precise, and safe technique for the reduction of low to moderate corneal astigmatism during cataract surgery.